2016
DOI: 10.1016/j.chemosphere.2015.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Thermal dechlorination of PCB-209 over Ca species-doped Fe2O3

Abstract: h i g h l i g h t s• 1% mol Ca species enhanced the activity of Fe 2 O 3 in the degradation of DecaCB.• Dominant Nona-MonoCB isomers were determined during hydrodechlorination reaction.• Thermodynamic and/or steric effects drive conversion.• Steric effect prevented the hydrodechlorination at ortho-positions. a r t i c l e i n f o b s t r a c tDegradation reaction of decachlorobiphenyl (PCB-209) was investigated over the synthesized Ca speciesdoped Fe 2 O 3 at 300°C. The 1%Ca-Fe 2 O 3 exhibited the highest act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Along with metallic Ca, other Ca compounds were tested in a hydrodechlorination process: Ca(OH) 2 [92], CaO [93][94][95] or CaSiO 3 [95]. Although most of these studies favored a radicalic mechanism, Gao and coworkers [95] discussed alternative pathways that involved either an electron transfer (with subsequent formation of a radical-anion that expels the chlorine anion and form the aryl radical) or a direct hydrogen transfer (in an S RN 1-type mechanism).…”
Section: Organochlorinementioning
confidence: 99%
“…Along with metallic Ca, other Ca compounds were tested in a hydrodechlorination process: Ca(OH) 2 [92], CaO [93][94][95] or CaSiO 3 [95]. Although most of these studies favored a radicalic mechanism, Gao and coworkers [95] discussed alternative pathways that involved either an electron transfer (with subsequent formation of a radical-anion that expels the chlorine anion and form the aryl radical) or a direct hydrogen transfer (in an S RN 1-type mechanism).…”
Section: Organochlorinementioning
confidence: 99%
“…It has been reported that competition between hydrodechlorination and oxidation reactions often occurs during the degradation of chlorinated aromatic hydrocarbons over metal oxides. 10,61,62 Several studies have reported that the surface oxygen of metal oxides can attack the aromatic ring, thereby resulting in oxidation reactions. 8,12 Based on the characteristics of the XPS spectra, reactive oxygen species, such as O 2 In order to further determine the oxidation products, the produced organic acid products after the degradation of CN-1 over γ-Al 2 O 3 were detected by IC.…”
Section: Degradation Product Analysismentioning
confidence: 99%